The Triassic-Jurassic Fundy Basin, eastern Canada: regional setting, stratigraphy and hydrocarbon potential - Wade, John; Brown, David; Traverse, Alfred; Fensome, Robert (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1996)
Fundy Basin, one of a series of half graben that formed along the eastern margin of North America during the Triassic/Jurassic rifting of Pangaea, lies mainly to the south of the Cobequid-Chedabucto Fault System in Nova Scotia and' beneath the Bay of Fundy. Continental red clastic rocks and basalt flows of the Triassic and Early Jurassic Newark Supergroup crop out continuously along the Bay of Fundy and Minas Basin coast of Nova Scotia and at several sites in southern New Brunswick. These units thicken beneath the waters of the bay to a present-day maximum of nearly 10 km. Proximal facies preserved along the faulted New Brunswick margin of the basin consist of upper alluvial fan and fluvial elastics which grade laterally into sheet flood deposits. Along the gently north-dipping Nova Scotia margin, facies consist of distal alluvial fan, sheet flood and playa mud flat deposits. Facies projections suggest the probability that petroleum-generating lacustrine sequences are widespread along the basin axis. In the Wolfvilte Formation and lower part of the Blomidon Formation these may be overmature but the upper part of the Blomidon Formation and the Scots Bay Formation have the potential for appreciable quantities of hydrocarbons.